7TH GRADE ZOOLOGY IN THE DEPARTMENT OF "SIMPLE ANIMALS" LEARNING USING MODERN ELECTRONIC RESOURCES. (Conference Zone, 2021)
The use of pedagogical, modern information technologies has been identified as an important task in improving the effectiveness of the teaching process in the education system. This article discusses how to increase students' interest, knowledge and thinking in the use of modern electronic resources, ICT, multimedia, interactive methods, pisa assignments, QR CODE and quiz, IQ tests in 7th grade zoology classes in secondary schools. Today, the use of electronic resources is becoming a modern requirement. We live in an era of rapid growth of scientific knowledge. From the point of view of system analysis, the educational process in secondary school and scientific knowledge is complex, infinite, interconnected systems, and the educational process is included in the system of scientific knowledge. Therefore, the rapid growth of scientific knowledge will inevitably increase the naturalness of the learning process and the quality and efficiency of the learning process. The use of interactive methods allows students to interact, work collaboratively, and think. Students will also be interested in science videos, including the use of computers in zoology classes, the use of various technological methods, and videos showing the animals' habitats, distribution, movement, and nutrition.